2020
DOI: 10.1007/s00068-020-01450-w
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of 15 years of horse-related maxillofacial fracture data at a major German trauma center

Abstract: Purpose The purpose of this study was to estimate the effect of the mechanism of trauma (fall versus kick), rider demographics, equestrian experience, protective equipment, and whether or not a horse was shod on the anatomic site of a horse-related maxillofacial fracture, operating time, postoperative complication rate, and length of hospital stay. Methods We retrospectively reviewed the medical records of patients treated for horse-related maxillofacial fractures at a single institution in Germany between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…As demonstrated in past studies on camel-related injuries, all patients in the current study were males, most being young camel caregivers (80.6%) from the Indian subcontinent [ 1 , 5 ]. This is in contrast to reports on horse-related injuries that showed that injuries were more prominent among females [ 11 , 12 , 13 ]. Camel caregiver populations are low-income workers with low educational levels but with a good background and some skills in animal care in their home countries.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As demonstrated in past studies on camel-related injuries, all patients in the current study were males, most being young camel caregivers (80.6%) from the Indian subcontinent [ 1 , 5 ]. This is in contrast to reports on horse-related injuries that showed that injuries were more prominent among females [ 11 , 12 , 13 ]. Camel caregiver populations are low-income workers with low educational levels but with a good background and some skills in animal care in their home countries.…”
Section: Discussioncontrasting
confidence: 99%
“…The median (range) ISS was 4.5 , and the median (range) GCS was 15 (10)(11)(12)(13)(14)(15). Twenty-three (63.9%) patients had an injury to another body region besides the face.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not have information on the riding level of the ridders who suffered trauma. Studies have shown that more than 70% of injuries occur in more experienced ridders (advanced or professional level) [6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The work by Stier et al . [ 4 ] underlines the necessity of a proper equipment and clearly shows the interdependency regarding the severity of the injury intensity. Finally, the manuscript by Rozema et al [ 5 ] brings evidence, that a systematic approach for examination is necessary in managing maxillofacial traumas in order to achieve the best possible outcome in making a decision, while reducing the number of unnecessary and time consuming diagnostic tools and steps.…”
mentioning
confidence: 99%